The isolation of lignin with native-like structure - Wang, Zhiwen; Deuss, Peter J. (Biotechnology advances, 2023)
Searching for renewable alternatives for fossil carbon resources to produce chemicals, fuels and materials is essential for the development of a sustainable society. Lignin, a major component of lignocellulosic biomass, is an abundant renewable source of aromatics and is currently underutilized as it is often burned as an undesired side stream in the production of paper and bioethanol. This lignin harbors great potential as source of high value aromatic chemicals and materials. Biorefinery schemes focused on lignin are currently under development with aim of acquiring added value from lignin. However, the performance of these novel lignin-focused biorefineries is closely linked with the quality of extracted lignin in terms of the level of degradation and modification. Thus, the reactivity including the degradation pathways of the native lignin contained in the plant material needs to be understood in detail to potentially achieve higher value from lignin. Undegraded native-like lignin with an as close as possible structure to native lignin contained in the lignocellulosic plant material serves as a promising model lignin to support detailed studies on the structure and reactivity of native lignin, yielding key understanding for the development of lignin-focused biorefineries. The aim of this review is to highlight the different methods to attain “native-like” lignins that can be valuable for such studies. This is done by giving a basic introduction on what is known about the native lignin structure and the techniques and methods used to analyze it followed by an overview of the fractionation and isolation methods to isolate native-like lignin. Finally, a perspective on the isolation and use of native-like lignin is provided, showing the great potential that this type of lignin brings for understanding the effect of different biomass treatments on the native lignin structure. •Collection of methods involving the isolation of lignin with a native-like structure;•Retention of the alkyl aryl ether linking motif is used as the key benchmark.•Balance between lignin quality and intensity of the isolation is of significance.•Guidelines for method selection to isolate native-like lignin are provided.